PENGARUH DETERMINAN P/E DAN P/E RASIO TERHADAP KEPEMILIKAN INSTITUSI : STUDI DI BURSA EFEK INDONESIA TAHUN 2004-2008 - Anggraini, Mita; Mahastanti, Linda Ariany (Jurnal Manajemen dan Keuangan, 2012)
Institutional investors needs analysis in making decisions for investing activities. Analysis of the most widely used is the fundamental analysis approach is through a P/E ratio. P/E (price earnings ratio) can be interpreted as an indicator of market confidence in the companys growth prospects in the future. High P/E indicates that the better performance of the company and this caught a lot of institutional investors to buy shares so that the percentage of institutional ownership in the company will be many. And investor institutions have hope will get high profit. The factors that influence the P/E has significance for investors before making an investment decision. Because of these factors predicted to influence the rise and decline of P/E. This study aims to determine the effect of P/E and P/E determinant of institutional ownership. This study uses panel regression analysis model to analyze the data using 25 sample manufacture companies listed on stock exchanges of Indonesia. The result indicated that DPR does not affect the P/E ratio, ROE affect the P/E ratio but has a negative coefficient, variable BV did not affect the P/E ratio and P/E ratio does not affect ownership of the institution ownershipKey words: the determinant of P/E, P/E ratio and institutional investors